STUDY OF GENETIC DIVERGENCE IN SWEET SORGHUM [SORGHUM BICOLOR (L.) MOENCH] - DHEERAJ SHINDE; SMITA CHAVAN; B. D. JADHAV (The Bioscan, 2012)
Genetic diversity is an essential prerequisite for improving the genetic makeup of any cop. Inclusion of genetically diverse parents in hybridization programme helps in isolation of superior recombinants. So, an experiment was conducted to investigate the genetic diversity among 46 genotypes of Sweet Sorghum [Sorghum bicolor (L.) Moench] against the thirteen growth characters mostly at maturity that has effect on ethanol production. Present study reveals that the clustering pattern based on D2 statistics grouped 46 genotypes into 11 clusters, out of which cluster I shows the highest intra cluster value (13.79) followed by cluster II (13.64) while maximum inter cluster distance (i.e. 34.72) was observed between cluster V and cluster IX, indicating there is presence of wide range of genetic diversity among the sweet sorghum genotypes. Such genotypes with wide genetic diversity based on their mean values can either be utilized for breeding programmes for genetic improvement in sweet sorghum or directly adopted as a variety.